Dietary exposure of Finnish children to heavy metal mixture – a cumulative assessment. Issue 5 (4th July 2017) - Suomi, Johanna; Tuominen, Pirkko; Savela, Kirsti
ABSTRACT: A preliminary assessment of the cumulative exposure to heavy metals among Finnish preschool children is reported. Cadmium, lead, arsenic, and mercury affect many of the same organs in the human body. The effects are mostly caused by oxidative stress or disruption of enzyme function. The cumulative effects of the heavy metals on the central nervous system and on the kidneys are determined based on national concentration and consumption data, and comparison of the relative toxicity of the heavy metals is based on dose–response values found in the literature. The cumulative effects were assumed to be additive. The main contributors to kidney toxicity among the studied population groups were cadmium and lead, while lead was the main contributor to neurotoxic effects.